Validation of a modified ETDRS chart for European-wide use in populations that use the Cyrillic, Latin or Greek alphabet - Sotiris Plainis; Joanna Moschandreas; Trisevgeni Giannakopoulou; Vania Vitanova; Panagoula Nikolitsa; Jos J. Rozema; Marie-José Tassignon; Miltiadis K. Tsilimbaris; Ioannis G. Pallikaris (Journal of Optometry, 2013)
Purpose: To validate a modified ETDRS visual acuity (VA) chart developed for European-wide use, in populations that use the Cyrillic, Latin or Greek alphabet. Methods: The charts were validated in three groups: 310 school children in Bulgaria (mean age 13 ± 1 years), 227 school children in Greece (mean age 14 ± 1 years) and 85 patients with no ocular pathology in Belgium (mean age 26 ± 5 years). VA was assessed with the habitual refractive correction, using the standard ETDRS charts and the modified European-wide charts. The intra-class correlation coefficient (ICC) was used to assess the test–retest reliability of the European-wide chart. The Bland–Altman comparison method was used to assess agreement between the two different versions of the new chart, as well as to compare these to the standard ETDRS-charts. Limits of agreement were calculated for differences in VA scores (test–retest variability (TRV)) between measurement sessions for the European-wide charts. Results: The TRV of the European-wide charts was found to be ±0.10 logMAR, corresponding to 5 ETDRS letters, for both chart 1 and chart 2. The ICC was estimated to be 0.968 for the RE and 0.961 for the LE. The European-wide charts generated on average slightly higher logMAR scores compared to the standard ETDRS charts in all three groups. Conclusions: The “European-wide” charts appear to be a valid alternative to the standard ETDRS acuity charts, offering the advantage of containing letters readable by all European citizens.